2001
DOI: 10.2169/internalmedicine.40.135
|View full text |Cite
|
Sign up to set email alerts
|

Susac's Syndrome: Beneficial Effects of Corticosteroid Therapy in a Japanese Case.

Abstract: Susac's syndromeis a rare disorder characterized by the triad of microangiopathy of the brain and retina with hearing loss. More than 50 affected individuals have been reported worldwide, all Caucasians. Weherein identify the first Japanese patient with Susac's syndrome. A 36-yearold mandeveloped recurrent subacute encephalopathy, bilateral sensorineural hearing loss, and retinal arteriolar occlusions, caused by microangiopathy from a year previously. T2-weighted MRIshowed multiple high-signal lesions predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Our understanding of the natural history of SS is also incomplete and is based primarily on anecdotal information [5][6][7][8][9][10][11][12][13][14][20][21][22][23][24][25]. SS tends to follow one of three major clinical courses: monocyclic, polycyclic, and chronic continuous.…”
Section: Natural Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Our understanding of the natural history of SS is also incomplete and is based primarily on anecdotal information [5][6][7][8][9][10][11][12][13][14][20][21][22][23][24][25]. SS tends to follow one of three major clinical courses: monocyclic, polycyclic, and chronic continuous.…”
Section: Natural Historymentioning
confidence: 99%
“…Some patients have improved without receiving any immunosuppressive treatment [20]. Some patients have responded very well to prednisone alone or to prednisone in combination with pulses of methylprednisolone [21][22][23]. Others have responded to a combination of prednisone and IVIG [23].…”
Section: Treatmentmentioning
confidence: 99%
“…The patient was also started with ticlopidine 300 mg/day and diltiazem 200 mg/day. Two years on these agents resulted in no further relapses and near baseline functionality [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…By four months, the patient had recovered completely, and his rash had resolved [15]. Tashima et al (2001) reported a case of a 36-year-old male with subacute onset encephalopathy, visual deficits, and bilateral hearing loss. CSF studies revealed an elevated protein of 288 mg/dl and an IgG level of 16.4 mg/dl.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Basierend auf der Hypothese einer Immunpathogenese und gestützt durch das anekdotisch berichtete Ansprechen auf immunsuppressive Therapien kommen überwiegend immunsuppressive Strategien zum Einsatz (31,(40)(41)(42)(43)(44) Literatur…”
Section: Verlauf Und Prognoseunclassified